Efficacy of topical 5% fluorouracil (5%- FU) needling in vitiligo - Ibrahiem, Mai Abdulkhaliq; Ismaiel, Mohammed Adel (Journal of medical and pharmaceutical sciences, 2021)
Objective: The aim of this study is to assess the efficacy of topical 5- fluorouracil (5%- FU) with micro needling in treating stable vitiligo. In addition to, assessment the side effects of the treatment. Patients and Methods: A Prospective study (Before& After) conducted for the period one year (April 2019- April2020)at Tishreen University Hospital in Lattakia- Syria, 31 patients with stable vitiligo who received treatment with micro needling and topical 5- fluorouracil (5%- FU) were included in this study. Results : The median age was 36 years, 67.70% of patients were female. Focal type was found in 61.3%, and most common sites of vitiligo involvement were hand and feet (33.7%), followed by trunk (24.8%)and extremities (24.8%). After 6 months of treatment, improvement was excellent in 63.4%, and very good in 23.8%. The lesions of neck and trunk were responded better to treatment than those in other parts of the body. Regarding of side effects, pain, erythema, and itching were reported in 100% followed by ulceration in (16.1%). Conclusion: Topical 5%- fluorouracil (5%- FU) with needling appears to be an effective and safe method in treating stable vitiligo. Except of pain, erythema, and itching after procedure, significant complications not occurred in most patients.